The importance of variability (flexibility) in multi-family apartment buildings - Gjorgji Dimkov, Dimitar Papasterevski (TTEM, 2021)
The variability of building structures can be achieved from the outside and inside, as well as with extensions or partitions. The degree of variability is proportional to the independence of the primary from the secondary structure. The relationship between the structure and the role of installations in the practical application of flexibility has been considered in a number of studies (SAR method, etc.), and all come to the conclusion that it is necessary not only to differentiate the primary from the secondary structure, but also to make the installations less fixed. However, differentiation does not mean that development can be inconsistent. The main mistake of the current development in construction technologies is in fact that there was a lack of relation to the secondary structure and that the connections in the construction process were not defined. Thus, the development of technology has limited the growth of the quality of housing, rather than improving it. Today the primary structures are built very quickly, their durability is practically unlimited, but if we compare them with the first beginnings of the application of the skeleton in residential construction with “endless possibilities”, burdened with various restrictions and regulations, today we have extremely unadjustable constructions, which do not allow nor minimum flexibility (similar to structures where a massive building system with load-bearing reinforced concrete walls is applied). This paper aims to provide a historical overview of research closely related to the importance of flexibility in multi-family apartment buildings in general, with reference to and analysis of experiences in the construction of flexible housing in the former SFR Yugoslavia.
Keywords: flexibility, multi-family residential buildings, variability